Encapsulating Cu2Se into 3D porous carbon as high-voltage electrode materials for aluminum-ion batteries. Issue 2 (15th January 2023) - Li, Jinjie; Kang, Lu; Luo, Ketong; Huang, Yanqun; Zhong, Shengkui; Yan, Dongliang
Abstract: In this work, a neoteric Cu2 Se@C positive electrode material for AIBs, which Cu2 Se nanoparticles encapsulated into three-dimensional (3D) porous carbon derived from HKUST-1 (MOF-199), has been fabricated through a synchronous carbonization-selenization strategy. Al/Cu2 Se@C batteries not only display high discharge plateau of 1.83 V and reversible capacity of 276.2 mA h g −1 under the current density of 200 mA g −1, but also show decent cycling stability with a retention of 54.4 mA h g −1 at 800 mA g −1 after 200 cycles. The good Al storage performance of Cu2 Se@C relies on its unique porous carbon structure, which plays an important role in improving the electrical conductivity of the electrode material, buffering the volume expansion, and providing channels for Al 3+ migration. A new opportunity toward the development of high performance and low cost AIBs is demonstrated in this work.